1999 Distinguished Service Award: Alice Horowitz, PhD - B. Alex White, DDS, DrPH (Blackwell Synergy, 2000)
The American Association of Public Health Dentistry’s Distinguished Service Award is presented to an in&- vidual for excellent and distinguished service to public health dentistry. This award is the highest honor the association can bestow. One need only review the names of past recipients to appreciate the level of commitment and distinguished service embodied in this award. It is indeed an honor and privilege to present the 1999 Distinguished Service Award to Dr. AIice Horowitz